Safety and immunogenicity of the CoV2-Bio in a healthy population aged 18 years and older in Indonesia - Maria, Suzy; Olfriani, Ciho; Koesnoe, Sukamto; Sekartini, Rini; Soedjatmiko; Medise, Bernie Endyarni; Yuniar, Irene; Indawati, Wahyuni; Wirahmadi, Angga; Sari, Rini Mulia; Adi, Nuri Purwito; Retnaningdyah, Windri (Medical Journal of Indonesia, 2025)
BACKGROUND According to the WHO Target Product Profiles for COVID-19 Vaccines, vaccine development should be indicated for active immunization in all populations, in conjunction with other control measures to curtail the pandemic. Several RBD-based COVID-19 vaccines are being evaluated and have shown advantages. CoV2-Bio was developed based on the wild-type SARS-CoV-2 RBD amino acid sequence, representing residues of the spike protein of the Wuhan-Hu-1 isolate. This study aimed to evaluate the safety and immunogenicity of CoV2-Bio when compared to CoronaVac. METHODS This was an observer-blinded, randomized controlled prospective study of safety and immunogenicity of the CoV2-Bio in healthy adult population. A total of 54 healthy participants were randomized to receive either 3 doses of CoV2-Bio or 2 doses of CoronaVac, and 1 dose of placebo, administered 28 days apart. Participants were followed up for safety and immunogenicity. IgG antibody titers (ELISA) and neutralization assay against Wuhan and Delta strains were evaluated at baseline, Days 28, 56, and 84. We assessed seropositive rate, seroconversion, and GMT as parameters. RESULTS Both vaccines were well tolerated and induced good antibody response. The incidence rate and intensity of local and systemic adverse events did not differ between vaccine and control groups. The vaccine group showed a larger proportion of seroconversion (4-fold increase antibody) (87.5% versus 46.2%, p = 0.001) and higher GMT (305.9 AU/ml versus 102.4 AU/ml, p<0.001) when compared to control group. CONCLUSIONS 3 doses of the CoV2-Bio are safe and immunogenic in healthy adult population. 3 doses of the CoV2-Bio COVID-19 vaccine produce a better immunogenicity profile compared to CoronaVac.